Class Background, Reception Context, and Intergenerational Mobility: A Record Linkage and Surname Analysis of the Children of Irish Immigrants. Issue 1 (March 2020) - Connor, Dylan Shane
Proponents of restrictive immigration policies often claim that families arriving with fewer skills and resources will struggle economically. This claim is challenging to test as lower-skilled migrants also tend to face greater discrimination, exclusion, and obstacles in the United States. I use unique multigenerational data on Irish Americans in the early-twentieth century, before and after migration, to directly study how the economic origins of Irish families and the reception context they faced in the United States affected economic attainment in the second generation. This analysis finds weak associations between economic background in Ireland and second-generation earnings in the United States. The schooling context and ethnic communities of settlement locations in the United States, in contrast, have strong effects on the second generation. These findings indicate that the experiences of immigrant families in the United States may be more important for second-generation attainment than the skills and resources brought from the origin country in the immigrant generation.